Microlithography and Metrology in Micromachining II 1996
DOI: 10.1117/12.250944
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of composite x-ray masks by micromilling

Abstract: An important aspect for the development of micromanufactured components and systems is to reduce the time and cost required to reach the prototype stage. At present, this development typically spans several years. Any fabrication approach which would reduce the cost and time-to-prototype would allow for the more rapid development of design concepts and the more rapid evolution of the design cycle. Direct fabrication of masks for X-ray lithography, by mechanical micromilling, is one potential avenue for rapid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Micromachining utilizes miniature milling, drilling and turning tools as small as 10 mm in diameter to produce micro-scale features. Although geometric and material capabilities of micromachining have been demonstrated by various researchers [5][6][7][8][9][10][11][12][13][14], industrial application of micromachining has been hindered by the lack of experience and knowledge on the micro-machinability of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Micromachining utilizes miniature milling, drilling and turning tools as small as 10 mm in diameter to produce micro-scale features. Although geometric and material capabilities of micromachining have been demonstrated by various researchers [5][6][7][8][9][10][11][12][13][14], industrial application of micromachining has been hindered by the lack of experience and knowledge on the micro-machinability of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Test exposures were made with varying thicknesses of commercially available (Goodfellow) graphite sheets. It was found that a thickness of less than 250 micrometers gave sufficient transmission of the x-rays to allow for timely exposures [Coane and Friedrich (1996)]. …”
Section: Mask Developmentmentioning
confidence: 99%